Richard Clinton, William S. Flash y R. Kennet Godwin (comps.), Political Science in Population Studies, Massachusetts, Lexington Books, 1972. XVIII, 154 p. - Reyna, José Luis (Estudios Demográficos y Urbanos, 1973)
RICHARD CLINTON, WILLIAM S. FLASH y R. KENNET GODWIN (Comps.) J Political Science in Population Studies, Massachusetts Lexington Books, 1972.